2012
DOI: 10.2164/jandrol.110.012351
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Imbalances and Psychological Scars Left Behind in Infertile Men

Abstract: The effect of infertility on the psychological well-being of couples has been the subject of increasing attention in recent years. The frustration of couples of a relatively young age (ie, in their fourth decades) provokes not only anxiety and depression but also negative effects on the relationships. The objective of this study was to evaluate the effect of a diagnosis of male infertility on anxiety and depression in the men themselves and in fertile female spouses. The prospective cross-sectional study consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 54 publications
(63 reference statements)
0
37
0
Order By: Relevance
“…There may be some question about our choice of decoy items, as there is ongoing research of the associations with infertility. Insomnia, for example, has been shown to be associated with an infertility diagnosis (Bak et al, 2012). However, as the decoy items did not factor into our overall knowledge scores, they did not impact our results.…”
Section: Discussionmentioning
confidence: 72%
“…There may be some question about our choice of decoy items, as there is ongoing research of the associations with infertility. Insomnia, for example, has been shown to be associated with an infertility diagnosis (Bak et al, 2012). However, as the decoy items did not factor into our overall knowledge scores, they did not impact our results.…”
Section: Discussionmentioning
confidence: 72%
“…A total of 17 studies measured depression among infertile couples using a variety of instruments: the Beck Depression Inventory (Bak et al, 2012;Chachamovich et al, 2010;Cserepes et al, 2013;Edelmann and Connolly, 2000;Galhardo et al, 2011;Gü leç et al, 2011;Karlidere et al, 2007;Pinto-Gouveia et al, 2012;Sultan and Tahir, 2011), the Self-Rating Depression Scale (Liu and Zhao, 2011), the Depression, Anxiety, and Stress Scale (Musa et al, 2014), the Brief Symptom Inventory (Brucker and McKenry, 2004), the Hospital Anxiety and Depression Scale (Anderson et al, 2003;Fatoye et al, 2008;Slade et al, 2007), the Symptom Checklist (Wischmann et al, 2009), and the Center for Epidemiologic Studies Depression Scale (Maximova and QuesnelVallé e, 2009).…”
Section: Depressionmentioning
confidence: 99%
“…As a consequence, the decision of raising a mixed gonadal dysgenetic patient as male cannot be based on a hypothetical fertility potential. Moreover, several publications have demonstrated that impaired fertility and short stature, each considered individually, are responsible for negative psychosocial outcomes in adult men (35,36,37).…”
Section: Patient Gh Therapymentioning
confidence: 99%